The Influence of Brand Image, Product Quality, and Price on Purchase Interest in Scarlett Products in Bengkulu City - Dwi Hanuarsyah; Sri Handayani; Andriyani Prawitasar (Penerbit Jurnal Indonesia, 2024)
The purpose of this research is to determine the influence of Brand Image, Product Quality and Price on Interest in Purchasing Scarlett Products in Bengkulu City. This type of research is a quantitative and casual type of research. The data collection method in this research uses observation and questionnaire techniques, with a sample of 105 respondents. The research results show that multiple linear regression Y = 22.739 + 0.146 (X1) + 0.270 (X2) + 0.153 (X3) + 4.056. Where the coefficient is positive, meaning that there is a positive or unidirectional relationship between the brand image variable (X1) and product quality (X2) with a value of zero, then buying interest has increased by 0.153. The coefficient is positive, meaning that there is a positive or unidirectional relationship between price (X3) and interest in buying Scarlett products in Bengkulu City. The results of the brand image test (X1) show tcount 2.418 > ttable 1.983 and significance 0.007 ttable 1.983 and 1 significance 0.000 ttable 1.983 and significance 0.005 2.46, so it is concluded that the hypothesis is accepted, meaning that there is a simultaneous influence between brand image (X1), product quality (X2) and price (X3) on interest in buying Scarlett products in Bengkulu City (Y ). This can be seen at the significance level of 0.000 <0.05.